Heterogeneous aging of large‐scale flexible lithium‐ion batteries based on micro‐heterostructures and simulation - Hong, Yinghao; Zheng, Jieqing; Deng, Dingrong; Wu, Qihui; Shen, Wenfeng (International journal of energy research, 2020)
Summary To meet application demands of electric vehicles, cathode materials of batteries have to overcome the life limitation and performance attenuation caused by crack propagation on the surface of electrode particles. With the increase of size and power of batteries, the voltage gradient generated by metal foil current collectors with high conductivity cannot be neglected. This study reconstructed a porous microstructure based on images of surface morphologies of lithium manganese oxide particles collected by a field emission‐scanning electron microscope. Based on this, a multi‐scale and multi‐physics simulation model coupling electro‐chemo‐thermo‐mechanical behaviours was developed to predict heterogeneous mechanical stress and capacity loss of a large‐scale flexible lithium‐ion battery. The results arising from use of the model show that: (1) Lithium in electrode particles cannot be diffused in time under a high‐charge and discharge rate, and the capacity loss of the battery is directly proportional to the stress generated on the electrode particles. Capacity loss at discharge rate of 10C is 46% higher than that at the rate of 1C and corresponding stress in the microstructure increases by 16%. (2) In the design of the battery layout adopted in this study, utilization rates of electrodes and temperature fields are highly heterogeneous at the higher rate. Mechanical stress near the tab is 8% higher than that at the bottom edge, and it is speculated that the rate of aging of the tab is 35% higher. (3) Mechanical stress during lithium extraction in the cathode during charge is less than half of that during discharge. Attributed to small influences of material activity and excellent performance of lithium titanate oxide in the anode, capacity loss during charge is only 2%. (4) During discharge, stress in the contact region of between particles is the largest, resulting in the decrease of the activity and the low lithium‐ion concentration. This leads to cracks during cyclic charging and discharging, which further decreases the activity of the materials. (5) Heterogeneity in the distribution of lithium‐ion concentration with different sizes of particles significantly rises with the rate. The model built in this research couples the analysis of temperature field of a battery cell and stress field of the microstructure, which is conducive to understanding mechanisms underlying performance attenuation of the large‐scale flexible lithium‐ion battery under high‐rate use.